2022
DOI: 10.1111/sms.14225
|View full text |Cite
|
Sign up to set email alerts
|

Associations between biological maturity level, match locomotion, and physical capacities in youth male soccer players

Abstract: Introduction Biological maturity level has shown to affect sport performance in youths. However, most previous studies have used noninvasive methods to estimate maturity level. Thus, the main aim of the present study was to investigate the association between skeletal age (SA) as a measure of biological maturation level, match locomotion, and physical capacity in male youth soccer players. Method Thirty‐eight Norwegian players were followed during two consecutive seasons (U14 and U15). Match locomotion was ass… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 42 publications
(70 reference statements)
0
1
0
Order By: Relevance
“…Our results showed a relationship between BA and running speed and jumping performance among the Icelandic players. This is in accordance with previous findings among Norwegian players at the same age ( 19 , 20 ) and confirms previous findings regarding the effect of biological maturation on speed and explosive leg strength ( 17 , 18 , 21 , 22 ). Our findings indicate that biological maturity level affects physical capacity among Icelandic youth soccer players, as has been demonstrated in other countries.…”
Section: Discussionsupporting
confidence: 93%
See 2 more Smart Citations
“…Our results showed a relationship between BA and running speed and jumping performance among the Icelandic players. This is in accordance with previous findings among Norwegian players at the same age ( 19 , 20 ) and confirms previous findings regarding the effect of biological maturation on speed and explosive leg strength ( 17 , 18 , 21 , 22 ). Our findings indicate that biological maturity level affects physical capacity among Icelandic youth soccer players, as has been demonstrated in other countries.…”
Section: Discussionsupporting
confidence: 93%
“…Furthermore, there was no relationship between BA and endurance capacity among the Icelandic players. This is also in line with previous findings among Norwegian U14 soccer players ( 19 , 20 ), and indicates that endurance capacity is not influenced by biological maturity status in highly trained youth soccer players. However, a recent investigation suggests that the positive change in VO 2max was paralleled by the increase in fat-free mass.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…In these circumstances, young football players with an early growth spurt can gain an advantage in sports. A recent study confirmed the influence of biological maturity on the success of 14–15-year-old young soccer players, in which a significant relationship was demonstrated between the level of biological maturity and key parameters of physical match performance such as peak speed, distance covered at high speed, performance in a 40 m sprint, and the CMJ [ 39 ]. It is important to note that the positive effect of increased testosterone levels on athletic success may be related not only to the effects on physical parameters, but also to a range of psycho-emotional factors such as motivation, focus on success, and dominance [ 40 ].…”
Section: Discussionmentioning
confidence: 83%